PROGRAM PEMBELAJARAN KOSA KATA MELALUI PENDEKATAN KONTEKSTUAL BAGI SISWA TUNARUNGU KELAS II SDLB-B DI SLB NEGERI SUBANG - Wati, Nur Wendah (2013)
This study aims to make the vocabulary learning program for students with hearing impairment, as aguideline for teachers in developing the students with hearing impairment'vocabulary mastery, which is increasing the number of new vocabulary to understand the meaning of vocabulary through the contextual intruction. The method used in this research is a descriptive qualitative approach. Subjects were an hearing impairment teacher and two students with hearing impairment as a data source support. The data collection techniques used observation, interviews, and documentary study. The techniques of data analysis done by reduction, display and conclusion. The examination tecniques and validity of data used triangulation and member checks. The procedure of the study, the first phase viewed the objective conditions, factors supporting and inhibiting factors in vocabulary learning. The second phase analyzed the results of objective conditions and formulate a draft program. The third stage is validation. The next program after the end of the program was revised to be hypothetical. The findings of this study is that vocabulary learning have not been effort optimaly, soo needed a program as guiding for teacher to develop vocabulary. The conclusion of this study is the first, teacher has not done well assessment, the implementation of learning vocabulary becomes part of the thematic material and assessment conducted during the learning take place, and at the end of learning, media used by teachers and peers who understand to help a friend who does not understand is a supporter for the acquisition of vocabulary learning, and student motivation is a barrier to learning vocabulary. The second, compiled program consists of five chapters, the first chapter is introduction, the second chapter is two program content, the third is the implementation of learning plan, the fourth and fifth chapter are evaluation program cover. The program is recommended to be used to guide teachers in developing the students with hearning impairments' vocabulary mastery at the sites of learning vocabulary through contextual intruction.